2008
DOI: 10.2174/157488508785747899
|View full text |Cite
|
Sign up to set email alerts
|

Whos Winning the War? Molecular Mechanisms of Antibiotic Resistance in Helicobacter pylori

Abstract: The ability of clinicians to wage an effective war against many bacterial infections is increasingly being hampered by skyrocketing rates of antibiotic resistance. Indeed, antibiotic resistance is a significant problem for treatment of diseases caused by virtually all known infectious bacteria. The gastric pathogen Helicobacter pylori is no exception to this rule. With more than 50% of the world’s population infected, H. pylori exacts a tremendous medical burden and represents an interesting paradigm for cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 172 publications
0
26
0
Order By: Relevance
“…Considering the increasing resistance observed among H. pylori strains worldwide (38,81), therapeutic options are becoming significantly limited. Therefore, the aim of the present study was to evaluate the antimicrobial activity of OAKs against H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the increasing resistance observed among H. pylori strains worldwide (38,81), therapeutic options are becoming significantly limited. Therefore, the aim of the present study was to evaluate the antimicrobial activity of OAKs against H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…However, high rates of resistance have been reported for people with a history of metronidazole treatment (49). Given the immense challenge in rising antimicrobial resistance (38), there is an enormous need for new antibiotics for the treatment of H. pylori infection.…”
mentioning
confidence: 99%
“…For enterococci, it has been shown that MICs of linezolid-resistant isolates are highly correlated with the percentage of rRNA cistrons mutated (237). In a way similar to the rRNA case, the FQs which have dual targets in standard pathogens have only a single target (DNA gyrase) in both Mycobacterium tuberculosis and H. pylori (160) and do yield to single-step resistance (178,195).…”
Section: The Multitarget Hypothesismentioning
confidence: 99%
“…Clarithromycin acts by binding to the peptidyltransferase region of 23S rRNA, thereby inhibiting protein synthesis (Gerrits et al, 2006;Jones et al, 2008). The resistance to clarithromycin in H. pylori has been shown to be due to point mutations in the peptidyltransferase region of domain V of the 23S rRNA.…”
Section: Introductionmentioning
confidence: 99%